The Influence of Green Accounting, Environmental Performance, and Firm Size on Firm Value - Miranti, Fransiska; Irawan, Irawan; Puspitasari, Endah Yuni (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research investigates how green accounting, environmental performance, and company size impact the firm value of manufacturing companies in the basic materials sector. The study uses data from the Indonesia Stock Exchange (IDX) for the 2017–2023 period to explore the influence of these factors on investor perception. Methodology/approach: This study employs a quantitative, causal research design. Using purposive sampling, a sample of 16 companies was selected, yielding 112 panel data observations. The analysis was conducted using multiple linear regression in SPSS 25 on secondary data from annual reports, financial statements, and PROPER ratings. Results/findings: Although green accounting, environmental performance, and company size are proven to have a significant simultaneous effect on firm value, only green accounting and company size show a positive partial effect. Furthermore, the model has limitations, as the 12.2% Adjusted R² value implies that other unexamined factors play a much larger role in determining firm value. Conclusion: This study aimed to examine the effect of green accounting, environmental performance, and company size on firm value in manufacturing companies in the basic materials sector. The results show that green accounting and company size have a positive and significant impact on firm value, while environmental performance does not show a significant effect. Limitations: The study is limited to the basic materials sector and does not include other variables such as profitability, liquidity, or corporate governance, which may also affect firm value. Contribution: This research adds to the fields of environmental accounting and corporate finance by empirically showing how sustainability and firm traits can boost company value.